Cilka's journey [large type] - Morris, Heather (Screenwriter) (Morris, Heather. Tattooist of Auschwitz, 2019)
Cilka is just sixteen years old when she is taken to Auschwitz-Birkenau Concentration Camp in 1942, where the commandant immediately notices how beautiful she is. Forcibly separated from the other women prisoners, Cilka learns quickly that power, even unwillingly taken, equals survival. When the war is over and the camp is liberated, freedom is not granted to Cilka: She is charged as a collaborator for sleeping with the enemy and sent to a Siberian prison camp. But did she really have a choice? And where do the lines of morality lie for Cilka, who was sent to Auschwitz when she was still a child? In Siberia, Cilka faces challenges both new and horribly familiar, including the unwanted attention of the guards. But when she meets a kind female doctor, Cilka is taken under her wing and begins to tend to the ill in the camp, struggling to care for them under brutal conditions. Confronting death and terror daily, Cilka discovers a strength she never knew she had. And when she begins to tentatively form bonds and relationships in this harsh, new reality, Cilka finds that despite everything that has happened to her, there is room in her heart for love. From child to woman, from woman to healer, Cilka's journey illuminates the resilience of the human spirit and the will we have to survive.